(untitled) (Bangladesh Journal of Medical Microbiology, 2016)
A multiplex PCR assay was evaluated for diagnosis of diarrheagenic Escherichia coli in stool samples of patients with diarrhoea submitted to a diagnostic microbiology laboratory. Two procedures of DNA template preparationproteinase K buffer method and the boiling method were evaluated to examine isolates of E. coli from 150 selected diarrhoeal cases. By proteinase K buffer method, 119 strains (79.3%) of E. coli were characterized to various categories by their genes that included 55.5% enteroaggregative E. coli (EAEC), 18.5% enterotoxigenic E. coli (ETEC), 1.7% enteropathogenic E. coli (EPEC), and 0.8% Shiga toxin-producing E. coli (STEC). Although boiling method was less time consuming (<24 hrs) and less costly (<8.0 US / per test) but was less efficient in typing E. coli compared to proteinase K method (41.3% vs. 79.3% ; p<0.001). The sensitivity and specificity of boiling method compared to proteinase K method was 48.7% and 87.1% while the positive and negative predictive value was 93.5% and 30.7%, respectively. The majority of pathogenic E. coli were detected in children (78.0%) under five years age with 53.3% under one year, and 68.7% of the children were male. Children under 5 years age were frequently infected with EAEC (71.6%) compared to ETEC (24.3%), EPEC (2.7%) and STEC (1.4%). The multiplex PCR assay could be effectively used as a rapid diagnostic tool for characterization of diarrheagenic E. coli using a single reaction tube in the clinical laboratory setting. Bangladesh J Med Microbiol 2007; 01 (02): 38-42